2015
DOI: 10.1063/1.4923190
|View full text |Cite
|
Sign up to set email alerts
|

Ultra low 1/f noise in suspended bilayer graphene

Abstract: We have studied 1/f noise power SI in suspended bilayer graphene devices. Around the Dirac point, we observe ultra low noise amplitude on the order of f*SI/Ib2=10−9. The low frequency noise level is barely sensitive to intrinsic carrier density, but temperature and external doping are found to influence the noise power. In our current-annealed samples, the 1/f noise is dominated by resistance fluctuations at the contacts. Temperature dependence of the 1/f noise suggests the presence of trap states in the conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…Even for the widely studied graphene FET it is still unclear what the dominant contribution is to the 1/f noise. Conflicting claims exist, where some studies attribute the 1/f -noise in graphene transistors primarily to noise generated within the channel region [7][8][9], whereas other investigations indicate a strong contribution from the contacts [10][11][12]. This distinction has remained elu-sive to existing studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] due to the lack of a microscopic understanding of how processes characteristic to the metal-graphene junctions, in particular the current crowding effect [22][23][24][25][26][27], impact the nature and magnitude of 1/f noise.…”
Section: Introductionmentioning
confidence: 99%
“…Even for the widely studied graphene FET it is still unclear what the dominant contribution is to the 1/f noise. Conflicting claims exist, where some studies attribute the 1/f -noise in graphene transistors primarily to noise generated within the channel region [7][8][9], whereas other investigations indicate a strong contribution from the contacts [10][11][12]. This distinction has remained elu-sive to existing studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] due to the lack of a microscopic understanding of how processes characteristic to the metal-graphene junctions, in particular the current crowding effect [22][23][24][25][26][27], impact the nature and magnitude of 1/f noise.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the studies on graphene noise have been conducted on mechanically exfoliated single layer and bilayer devices [15,16,17,18,19]. It has been observed that the noise is usually smaller in bilayer structures compared to single layer devices.…”
Section: Introductionmentioning
confidence: 99%
“…The noise is dependent on the gate-induced carrier density and hence is expected to vary with the charge concentration at the surface [15]. Further, the noise magnitude has also been reported to depend on the disorder level, thickness of the grain boundaries [16] and also on the substrate on which it has been deposited [18,19]. Tan et al report that nanoribbons show lower flicker noise levels than planar graphene but the shot noise increases in graphene nanoribbons due to increased scattering in the presence of disordered edges [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The ten-fold increase in the upwards transition rate brings the value of τ 0 close to the value of τ s (see below), which means gradual overlapping of individual avalanche pulses. The second increase in low-f noise is assigned to the contacts, which are known to have low-frequency resistance fluctuations even in the case of the best suspended samples [39].…”
Section: Low Frequency Switching Noisementioning
confidence: 99%